“implementación de una metodología de calidad y productividad en una pyme del sector plástico” - Mora Hurel, Lisbeth (2010)
PLASTIC S.A. is a medium sized company dedicated to the manufacturing of plastic bag, rolls and plastic film since 1994. Unfortunately in recent years the company has faced problems of high level of waste, a high level of inventory and defective products. Those problems were mainly the consequence of the unorganized growth of the company. In order to reduce these problems, the general objective of this project is to implement techniques of continuous improvement targeted towards small and medium businesses, resulting in the increase of the levels of quality and productivity. The techniques implemented were: the 5's methodology, mapping work and expectations, teamwork, customer visits, cause-effect diagrams, failure modes and effects analysis and quality. These allowed workers to realize the importance of organization in the workplace, identify the main causes that generate the greatest impact on product quality in the area of extrusion such as, lumps, treatment failures, black dots and blocking, and integrate the sales and production departments. The project resulted in a continuing decrease of the total percentage of waste from 14% to 7.42%. Consumer claims and returns also saw the same results, reaching 0%.